Transparency of Village Budget Management in Ngaban Village, Tanggulangin Sub-district, Sidoarjo Regency - Savira, Adellia Nanda; Wibawani, Sri (International Journal of Economics Development Research (IJEDR), 2023)
The allocation of large funds as a hope that can put the welfare of villagers, and therefore in its management is required to apply the concept of good governance that can create prosperous and prosperous citizens using three principles, namely: 1) Transparency; 2) Accountability; 3) Community Participation. Village funds are one of the sources of problems for people to commit acts of corruption, because the realm is in small and remote areas so that it needs supervision in its allocation. There are cases of corruption in village funds, where the village funds are used and utilized to improve public services in the village. The category of corruption cases that has the highest number of cases is corruption of village funds. The existence of village funds makes a source of income for each village, including income for the Village Budget which is used as village development. Village development plays a very important role in the welfare of the community, therefore in the process a budget is needed to implement all development activity plans, the revenue and expenditure budget obtained by each village is a budget plan set by the Village Head. The village head is a village government official who has responsibility for the central and regional governments in exercising his authority, namely organizing village households. Of the several corruption cases in Sidoarjo, one of which occurred in Ngaban Village, Tanggulangin Subdistrict in 2021, where the village head embezzled 174 million for personal gain. The purpose of this study is to describe in depth the Transparency of Village Budget Management in Ngaban Village, Sidoarjo Regency. Using qualitative research methods has a descriptive nature and tends to use analysis. The results showed that the application of the transparency dimension has been carried out well in the transparency of village revenue and expenditure budget management in Ngaban Village, Sidoarjo Regency by the Ngaban Village Government. However, there are two indicators of the transparency dimension that have not gone well.